A comparison of dried shiitake mushroom in log cultivation and mycelial cultivation from different geographical origins using stable carbon and nitrogen isotope analysis - Suzuki, Yaeko; Nakashita, Rumiko; Ishikawa, Noemia Kazue; Tabuchi, Akiko; Sakuno, Emi; Tokimoto, Keisuke (Bunseki Kagaku, 2016)
We determined carbon and nitrogen isotopic compositions (δ13C and δ15N) of dried shiitake mushroom (Lentinula edodes) samples from Japan, China, South Korea and Brazil in order to discriminate their geographical origins. In log cultivation, the δ13C values of Japanese dried shiitake samples were lower than those of Chinese samples, depending on the δ13C values of log and their growth conditions. In mycelial cultivation, the δ13C and δ15N values of Japanese dried shiitake samples were higher than those of Chinese samples. By using the δ13C and δ15N values, 87.4 ％ of Japanese dried shiitake samples (n＝95) and 87.9 ％ of Chinese dried shiitake samples (n＝66) in log cultivation, 90.0 ％ of the Japanese dried shiitake samples (n＝50) and 93.9 ％ of Chinese dried shiitake samples (n＝114) in mycelial cultivation, were correctly classified according to the production site. These results suggested that the δ13C and δ15N values will be potentially useful for tracing their geographical origin of dried shiitake samples. © 2015 The Japan Society for Analytical Chemistry.